1996
DOI: 10.1149/1.1836615
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Corrosion of Aluminum in the Presence of Ammonium Sulfate Particles

Abstract: The effect of (NH4)2S04 particles on the atmospheric corrosion of aluminum has been investigated at 300 and 373 K at various relative humidity (RH) levels. Aluminum reacts with (NH4)2S04 particles only at or above the critical relative humidity (CRH) of (NH4)2S04 at either temperature. The corrosion rate increases with increasing RH and temperature. Above the CRH of (NH4)2S04, droplets are formed on the particles at both temperatures, making electrochemical reactions possible. The (NH4)2504 decomposes and ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…The rate of the OCP drop was calculated for four different tests; this rate decreased by a factor of ten between the two steps (5.6 Â 10 À3 mV/h for the first 24 h of immersion compared with 5.6 Â 10 À4 mV/h during the second step). The OCP drop at the beginning of the test could be linked to the dissolution of the protective oxide [27]. Importantly, Hagyard et al showed that the potential rose to a peak at the beginning of the immersion and that this increase was attributed to the dissolution of aluminum and to the formation of the protective oxide [28,29].…”
Section: Corrosion Susceptibility Of the 2050 Alloy During Continuous Immersion Testsmentioning
confidence: 99%
“…The rate of the OCP drop was calculated for four different tests; this rate decreased by a factor of ten between the two steps (5.6 Â 10 À3 mV/h for the first 24 h of immersion compared with 5.6 Â 10 À4 mV/h during the second step). The OCP drop at the beginning of the test could be linked to the dissolution of the protective oxide [27]. Importantly, Hagyard et al showed that the potential rose to a peak at the beginning of the immersion and that this increase was attributed to the dissolution of aluminum and to the formation of the protective oxide [28,29].…”
Section: Corrosion Susceptibility Of the 2050 Alloy During Continuous Immersion Testsmentioning
confidence: 99%
“…EDX analysis confirmed the presence of sulphur in felsobanyaite and sodium in dawsonite. Aluminium sulphate hydrates are common corrosion products on aluminium exposed to marine atmosphere [13] [14] [15]. Sulphates present in the solution are adsorbed on aluminium oxide layer [16] and converted into corrosion products.…”
Section: Resultsmentioning
confidence: 99%
“…When the cupric, sulfate, and hydroxyl ion concentrations are high enough to form posnjakite, this phase starts to precipitate on the cuprite surface. 8 As described above, there are two roles of oxidized sulfur species, including SO 2 and (NH 4 ) 2 SO 4 , in the early stage of copper patination. One is lowering the pH of the surface electrolyte, which accelerates the dissolution of the initially formed cuprite.…”
mentioning
confidence: 96%
“…29) As shown in Fig 10(b), posnjakite formed on cuprite. A posnjakite formation mechanism was proposed by Lobnig et al 8) and Odnevall et al 18) Odnevall et al showed that posnjakite forms on cuprite and that the existence of intermediate non-crystalline compounds composed of copper and sulfate are present before posnjakite formation. 18) Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation